Alexandrov-embedded closed magnetic geodesics on S2 - Schneider, Matthias (Ergodic theory and dynamical systems, 2011)
We prove the existence of two Alexandrov-embedded closed magnetic geodesics on any two-dimensional sphere with non-negative Gauß curvature.